PENGARUH SELF-EFFICACY TERHADAP PRESTASI BELAJAR IPS SISWA KELAS VIII SMP - Diaz Ayu Sudwiarrum; Nuryana Nuryana; Ratna Puspitasari (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2021)
This study aims to find out how the level of student self-efficacy, student achievement, and find out how much influence self-efficacy of class VIII students of SMP Negeri 2 Sumber Cirebon Regency has. Self-efficacy is the belief in one's ability to organize and carry out activities that are expected to achieve the goals that have been set. Learning achievement is the result of a learning system within a certain period of time which is recognized in values in the form of numbers and letters. The better the student's self-efficacy, the better the student's learning achievement, and vice versa. This research is a quantitative research. This exploratory configuration uses two sets of factors, namely variable X (self-efficacy) and variable Y (Learning Achievement). The research population was all students of class VIII at SMP Negeri 2 Sumber Cirebon, totaling 246 students who were selected by random sampling. Data collection techniques in this study used questionnaires and documentation studies. The data analysis technique used simple linear regression. The results of this study indicate that: (1) the self-efficacy level of students 69.18% is included in the fairly good category, (2) the student achievement level is 79.21% is included in the good category, (3) sig. 0.000, on the grounds that 0.000 <0.05 then Ho is rejected and Ha is accepted that there is an effect of self-efficacy on learning achievement, (4) the coefficient of determination (R2) 0.524 indicates that the level of commitment of the autonomous variable is 52.4%. This shows that 52.4% of learning achievement is influenced by self-efficacy, while 47.6% is influenced by different elements. Key Words: Learning Achievement, Self-Efficacy